Wireless instrumentation system based on dry electrodes for acquiring EEG signals - Dias, N. S. (2012)
This paper presents a complete non-invasive Wireless acquisition system based on dry electrodes for electroencephalograms (WiDE-EEG) with emphasis in the electronic system design. The WiDE-EEG is composed by a 2.4GHz radio-frequency (RF) transceiver, biopotential acquisition electronics and dry electrodes. The WiDE-EEG can acquire electroencephalogram (EEG) signals from 5 unipolar channels, with a resolution of 16bits and minimum analog amplitude of 9.98μV(pp), at a sampling rate of 1000samples/s/channel and sends them to a processing unit through RF in a 10m range. The analog channels were optimized for EEG signals (with amplitudes in the range 70-100μV) and present the following characteristics: a signal gain of 66dB and a common mode rejection ratio of 56.5dB. Each electrode is composed by 16 microtip structures that were fabricated through bulk micromachining of a 〈100〉-type silicon substrate in a potassium hydroxide (KOH) solution. The microtips present solid angles of 54.7°, a height of 100-200μm and 2μm spaced apart. The electrodes have a thin layer (obtained by sputtering) of iridium oxide (IrO) to guaranty their biocompatibility and improve the contact with the skin. These dry electrodes are in direct contact with the electrolyte fluids of the inner skin layers, and avoid the use of conductive gels. The complete WiDE-EEG occupies a volume of 9cm×8.5cm×1cm, which makes it suitable for true mobility of the subjects and at the same time allows high data transfer rates. Since the WiDE-EEG is battery-powered, it overcomes the need of galvanic isolation for ensuring patient safety observed on conventional EEG instrumentation systems. The WiDE-EEG presents a total power consumption of 107mW, divided as follows: the acquisition system contributes with 10mW per channel, whereas the commercial MICAz module contributes with 57mW (e.g., 24mW from the microcontroller and 33mW from the RF chip). The WiDE-EEG also presents autonomy of about 25h with two class AA 1.5V batteries.